A spirituality of dissent: Religion, culture and post-colonial criticism - Gearon, L (2001)
This paper examines one aspect of post-colonial criticism - the relationship between culture and its representation - and considers the relevance of this for understandin g children's spirituality in contemporary, global context. The paper provides particular focus on the now widely held premise in post-colonial criticism that domination within political and social systems is dependent upon the control and manipulation of cultural representation, with particular focus on the cultural representation of religion in British education. The crucial idea here is that such domination (including the disempowerment and subjugation of minorities) is dependent upon the creation of a culturally imagined 'other'. It is argued that this alienating socio-political and economic dimension of spirituality - and essentially colonial notion of 'otherness' - has largely been ignored in discussions of contemporary spirituality. The paper thus introduces into current debate the language of post-colonial criticism in order to demonstrate the inherent, if underplayed, politicization of spirituality. It concludes with a call to re-examine the representation of culture within a global, post-colonial framework through the characterization of a 'spirituality of dissent'. © 2001 Taylor and Francis Ltd.